2016
DOI: 10.5194/bg-13-1821-2016
|View full text |Cite
|
Sign up to set email alerts
|

Application of the <sup>15</sup>N gas-flux method for measuring in situ N<sub>2</sub> and N<sub>2</sub>O fluxes due to denitrification in natural and semi-natural terrestrial ecosystems and comparison with the acetylene inhibition technique

Abstract: Abstract. Soil denitrification is considered the most un-constrained process in the global N cycle due to uncertain in situ N2 flux measurements, particularly in natural and semi-natural terrestrial ecosystems. 15N tracer approaches can provide in situ measurements of both N2 and N2O simultaneously, but their use has been limited to fertilized agro-ecosystems due to the need for large 15N additions in order to detect 15N2 production against the high atmospheric N2. For 15N–N2 analyses, we have used an “in-hous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 59 publications
(11 reference statements)
3
48
0
Order By: Relevance
“…In the past, comparison of different methods to determine denitrification processes had always been complicated by the difficulty in keeping the soil conditions for the compared methods identical. 13,[29][30][31][32] This also applied to our study because we did not have the resources to conduct 15 NGF+ and conventional 15 NGF at exactly the same time. Figure 4), we showed that subsoil diffusion was indeed relevant in our setup.…”
Section: Comparison Of 15 Ngf+ With Reference Methods In the Field Ementioning
confidence: 99%
See 1 more Smart Citation
“…In the past, comparison of different methods to determine denitrification processes had always been complicated by the difficulty in keeping the soil conditions for the compared methods identical. 13,[29][30][31][32] This also applied to our study because we did not have the resources to conduct 15 NGF+ and conventional 15 NGF at exactly the same time. Figure 4), we showed that subsoil diffusion was indeed relevant in our setup.…”
Section: Comparison Of 15 Ngf+ With Reference Methods In the Field Ementioning
confidence: 99%
“…Underestimation of denitrification rates can occur because a certain fraction of the 15 Nlabelled denitrification products is not emitted from the soil surface, but diffuses to the subsoil. 13 When applying 15 NGF in the laboratory, the sensitivity can be augmented by incubation under an N 2 -depleted atmosphere in a closed system 14,15 or in an open system where the soil headspace is continuously flushed at a constant rate with an artificial N 2 -depleted atmosphere. 16 Direct measurement of N 2 fluxes using the He/O 2 method is not subject to the problems associated with 15 N-based methods, 17 but the need for sophisticated gastight incubation systems limits its use to laboratory incubations only and low N 2 fluxes are difficult to detect due to the difficulty in completely removing atmospheric N 2 .…”
mentioning
confidence: 99%
“…− production via nitrification, the possible slow diffusion of C 2 H 2 into fine textured soils and rapid decomposition of C 2 H 2 [44,[47][48][49]. Nonetheless, beyond this limitation of the method, the AIT has been effectively and widely used and recommended (also in recent pertinent literature) to compare sites and experimental treatments (in both terrestrial and aquatic environments) and to evaluate controlling factors [44,46,[50][51][52].…”
Section: Sampling and Processing Intact Soil Cores For Denitrificatiomentioning
confidence: 99%
“…Closing incubation vessels for a limited time and estimating denitrification from headspace concentration (e.g. Meyer et al, 2010;Siegel et al, 1982) inevitably lead to underestimation of denitrification rates. Experimental evidence for this underestimation was obtained by destroying pore structure at final sampling to homogenize headspace and pore space (Harter et al, 2016).…”
Section: Estimating Production Of N 2 and N 2 O Based On Surface Fluxmentioning
confidence: 99%
“…There are three principles to overcome the latter problem: (i) adding NO − 3 that is highly enriched in 15 N and monitoring 15 N-labelled denitrification products ( 15 N gas flux method; e.g. Siegel et al, 1982), (ii) adding acetylene to block N 2 O reductase quantitatively and estimating total denitrification from N 2 O production (acetylene inhibition technique, e.g. Felber et al, 2012), and (iii) measuring denitrification gases during incubation of soils in the absence of atmospheric N 2 using gas-tight containers and artificial helium-oxygen atmosphere (HeO 2 method; Scholefield et al, 1997;Butterbach-Bahl et al, 2002).…”
Section: Introductionmentioning
confidence: 99%